Apoptosis-Inducing Activity of Marine Sponge Haliclona sp. Extracts Collected from Kosrae in Nonsmall Cell Lung Cancer A549 Cells. (6th July 2015) - Bae, Woori; Lim, Hyun Kyung; Kim, Kyoung Mee; Cho, Hyosun; Lee, Sun Yi; Jeong, Choon-Sik; Lee, Hyi-Seung; Jung, Joohee
Abstract : Although various anticancer drugs have been developed for the treatment of nonsmall cell lung cancer, chemotherapeutic efficacy is still limited. Natural products such as phytochemicals have been screened as novel alternative materials, but alternative funds such as marine bioresources remain largely untapped. Of these resources, marine sponges have undergone the most scrutiny for their biological activities, including antiinflammatory, antiviral, and anticancer properties. However, the biological mechanisms of the activities of these marine sponges are still unclear. We investigated the anticancer activity of marine sponges collected from Kosrae in Micronesia and examined their mechanisms of action using nonsmall cell lung cancer A549 cells as a model system. Of 20 specimens, the Haliclona sp. (KO1304-328) showed both dose- and time-dependent cytotoxicity. Further, methanol extracts of Haliclona sp. significantly inhibited cell proliferation and cell viability. A549 cells treated with Haliclona sp. demonstrated induced expression of c-Jun N-terminal kinase (JNK), p53, p21, caspase-8, and caspase-3. The percentage of apoptotic cells significantly increased in A549 cultures treated with Haliclona sp. These results indicate that Haliclona sp. induces apoptosis via the JNK-p53 pathway and caspase-8, suggesting that this marine sponge is a good resource for the development of drugs for treatment of nonsmall cell lung cancer.